The Influence of Digital Advertising on Financial Service Purchase Intentions: The Role of Consumer Emotions and Trust Theoretical Model - Lubytė, Viltė; Jasinskas, Edmundas; Romeika, Giedrius (Vilnius University Proceedings, 2025)
The influence of digital advertising on financial service purchase intentions, mediated by consumer emotions and trust, is crucial in today’s digital landscape. Intense online competition requires financial service providers to understand digital advertising, emotions and trust impact on consumer intentions. The purpose of this study is to introduce this conceptual model, illustrating how digital advertising, viewed through message and source characteristics, impacts purchase intentions via consumer emotions and trust. Drawing on the RAIA model, the study conceptualises the consumer intention journey in the digital space, acknowledging the evolving information adoption landscape. The model differentiates between fear and greed as instantaneous emotional responses to advertising, rather than inherent consumer traits. Furthermore, it distinguishes mistrust as a separate construct from low trust, highlighting its significant impact on purchase intentions. The findings offer practical implications for marketers, researchers, and financial institutions seeking to develop effective digital advertising strategies grounded in the RAIA framework.